Analisis Curah Hujan Dan Risiko Banjir Di Ibu Kota Nusantara (IKN) Tantangan Dan Strategi Mitigasi - Anah, Lailatus Isti (JURNAL GEOGRAFI, 2025)
The relocation of Indonesia’s capital city to East Kalimantan presents new challenges, particularly in terms of disaster risk, including flooding. Land-use changes, deforestation, and high rainfall are key factors that may increase this risk. This study aims to analyze daily and monthly rainfall data in the surrounding areas of the new capital (IKN) from 2019 to 2024 to understand extreme rainfall patterns and their relation to flood potential. The method used is descriptive quantitative analysis based on rainfall data from BMKG stations closest to the IKN area. The data is analyzed to observe annual trends and variations in rainfall. The results are expected to provide an overview of the tendency for high rainfall and support data-driven flood mitigation efforts. These findings are important for spatial planning and the development of green infrastructure that is adaptive to climate change in the IKN region.